Improving link prediction models through a performance enhancement scheme:a study on semi-supervised learning and model soup - Qi Donglin; Chen Shudong; Du Rong; Yu Yong; Tong Da (中国邮电高校学报（英文版）, 2024)
As an important method for knowledge graph(KG)complementation,link prediction has become a hot research topic in recent years.In this paper,a performance enhancement scheme for link prediction models based on the idea of semi-supervised learning and model soup is proposed,which effectively improves the model performance on several mainstream link prediction models with small changes to their architecture.This novel scheme consists of two main parts,one is predicting potential fact triples in the graph with semi-supervised learning strategies,the other is creatively combining semi-supervised learning and model soup to further improve the final model performance without adding significant computational overhead.Experiments validate the effectiveness of the scheme for a variety of link prediction models,especially on the dataset with dense relationships.In terms of CompGCN,the model with the best overall performance among the tested models improves its Hits@1 metric by 14.7％on the FB15K-237 dataset and 7.8％on the WN18RR dataset after using the enhancement scheme.Meanwhile,it is observed that the semi-supervised learning strategy in the augmentation scheme has a significant improvement for multi-class link prediction models,and the performance improvement brought by the introduction of the model soup is related to the specific tested models,as the performances of some models are improved while others remain largely unaffected.